Pengaruh Pemberitaan Terorisme Di Media Terhadap Perilaku Beragama Di Masyarakat Desa Banjarwangi Kecamatan Ciawi Kabupaten Bogor - Muhamad Rizki Saepul Zamil; Nirwan Syafrin; Ikhwan Hamdani (Universitas Pahlawan Tuanku Tambusai, 2023)
With the birth of online media, the dissemination of information can be done quickly and can be accessed by anyone, anytime and anywhere. The community is also assisted by the development of this technology to get various kinds of news both political, economic, educational, criminal, cultural and even to the issue of terrorism. Reporting on terrorized causes anxiety for the community. However, The purpose of this research is to find out whether there is an influence from the news of terrorism on religious behavior in the people of Banjarwangi Village, Ciawi District, Bogor Regency. The theory used in this study is the theory developed by Melvin De Fleur, namely the S-O-R (Stimulus-Organism-Response) theory. This theory explains that changes in the communicant's attitude can occur if the stimulus given is stronger than what the communicant previously knew. In this study, the authors used a quantitative approach with a positivism paradigm. The author uses the questionnaire method as a means of measuring data collection. Then the sampling technique used was data processing by utilizing Microsoft Ecxel, and IBM SPSS Statistics 21 Software. Data analysis used a Simple Linear Regression Test to determine whether there was an influence of reporting on terrorism on the religious behavior of the people of Banjarwangi Village, Ciawi District, Bogor Regency. The results of the research show that the effect is very weak with a correlation value of 0.1%, namely there is no relationship between terrorism reporting in the media and the religious behavior. Keywords: terrorism; media; religious behavior; quantitative